Prevalence and Characterization of Staphylococcus aureus Cultured From Raw Milk Taken From Dairy Cows With Mastitis in Beijing, China - Wang, Wei; Lin, Xiaohui; Jiang, Tao; Peng, Zixin; Xu, Jin; Yi, Lingxian; Li, Fengqin; Fanning, Séamus; Baloch, Zulqarnain (Frontiers in Microbiology, 2018)
The colonization of dairy herds and subsequent contamination of raw milk by Staphylococcus aureus (S. aureus), especially those expressing a multi-drug resistance (MDR), biofilm and toxins producing ability, remains an important issue for both the dairy producer and public health. In this study, we investigated the prevalence, antimicrobial resistance, virulence, and genetic diversity of S. aureus in raw milk taken from 2 dairy farms in Beijing, China. Ninety(46.2%, 90/195) samples were positive for S. aureus. Resistant to penicillin (PEN) (31.3%), ciprofloxacin (18.8%) and enrofloxacin (15.6%) were the most often observed. Isolates cultured from farm B showed significantly higher resistance to penicillin (73.9%), ciprofloxacin (34.8%), enrofloxacin (34.8%), tilmicosin (17.4%), and erythromycin (17.4%) than those from farm A (p< 0.05). Totally, 94.8% S. aureus harbored at least one virulence gene and the pvl (93.8%), sec (65.6%), and sea (60.4%) genes were the most frequently detected. The pvl and sec genes were more often detected in isolates from farm A (97.3% and 84.9% respectively) than those from farm B (p< 0.05).Of all 77 staphylococcus enterotoxin (SE)-positive isolates, more than 90% could produce enterotoxins and 70.1% could produce two types. Biofilm related genes (icaA/D, clf/B, can, and fnbA) were detected in all96 isolates. All 96isolates could produce biofilm with 8.3%, 70.8%, and 18.8% of the isolates demonstrating weak, moderate and strong biofilm formation, respectively. A total of 5STs, 7 spa types (1 novel spa type t17182), 3agr types (no agrII), and 14 SmaI-pulso-types were found in this study. PFGE cluster II-CC1-ST1-t127-agr III was the most prevalent clone (56.3%). Isolates of agr III (PFGE Cluster I/II-CC1-ST1-t127/2279) had higher detection of virulence genes than those of agr I and agr IV. TheMSSA-ST398-t1456-agr I clone expressed the greatest MDRbut with no virulence genes andweakly biofilm formation.Our finding indicated a relatively high prevalence of S. aureus with less antimicrobial resistance but often positive for enterotoxigenicity and biofilm formation. This study could help identify predominant clones and provide surveillance measures to eliminate and decrease the contamination of S. aureus in raw milk of dairy cows with mastitis.